Self- assurance conception - Zaborowski, Zbigniew (Studia Psychologica: Theoria et praxis, 2002)
The article comprises an original conception of an important personality determinant,  underestimated by psychologists, i.e. self – assurance. The author differentiated between normal situations and abnormal situations and stated that self- assurance is often connected with normal situations. He presented a model of self- assurance in which external and social situations and inner state of health and apparition impact on personality. It is supposed that self- assurance could be a form of expression of self- consciousness and sense of internal external control or self- control. Self- assurance could also be limited by conflicts, dissonances and helplessness.